2018
DOI: 10.1016/j.smrv.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of dementia in obstructive sleep apnea

Abstract: Epidemiologic and mechanistic evidence is increasingly supporting the notion that obstructive sleep apnea is a risk factor for dementia. Hence, the identification of patients at risk of cognitive decline due to obstructive sleep apnea may significantly improve preventive strategies and treatment decision-making. Cerebrospinal fluid and blood biomarkers obtained through genomic, proteomic and metabolomic approaches are improving the ability to predict incident dementia. Therefore, fluid biomarkers have the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 113 publications
0
40
1
1
Order By: Relevance
“…Parts of the sample were included in previous papers by our group (Baril et al, ; Baril et al, ; Baril, Carrier, et al, ; Baril, Gagnon, et al, ; Gagnon et al, ; Gagnon et al, ; Gosselin et al, ). Exclusion criteria were as follows: neurological or psychiatric diseases, cerebrovascular diseases, dementia, history of traumatic brain injury, pulmonary diseases, sleep disorders other than OSA, being treated for OSA, morbid obesity (body mass index [BMI] >40), the usage of medication that influence sleep, breathing or brain functioning (e.g., benzodiazepines, anticonvulsants, sedatives, antidepressants, and antipsychotics), and drug and alcohol abuse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parts of the sample were included in previous papers by our group (Baril et al, ; Baril et al, ; Baril, Carrier, et al, ; Baril, Gagnon, et al, ; Gagnon et al, ; Gagnon et al, ; Gosselin et al, ). Exclusion criteria were as follows: neurological or psychiatric diseases, cerebrovascular diseases, dementia, history of traumatic brain injury, pulmonary diseases, sleep disorders other than OSA, being treated for OSA, morbid obesity (body mass index [BMI] >40), the usage of medication that influence sleep, breathing or brain functioning (e.g., benzodiazepines, anticonvulsants, sedatives, antidepressants, and antipsychotics), and drug and alcohol abuse.…”
Section: Methodsmentioning
confidence: 99%
“…Recent meta‐analyses concluded that OSA is a risk factor for cognitive decline and incident dementia (Leng, McEvoy, Allen, & Yaffe, ; Shi et al, ; Zhu & Zhao, ). These epidemiological findings have given rise to several mechanistic hypotheses linking OSA to neurodegeneration: OSA is associated with amyloid‐β generation and altered clearance, tau hyperphosphorylation, inflammation, oxidative stress, and metabolic and vascular deregulation (Baril, Carrier, et al, ; Baril, Gagnon, et al, ; Gosselin, Baril, Osorio, Kaminska, & Carrier, ; Polsek et al, ; Rosenzweig et al, ). In addition, OSA in late middle‐aged and older adults could precipitate the progression toward dementia by creating microstructural cerebral changes, especially white matter damage.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that the effects of sleep apnea on cognition are more pronounced in APOE4 gene carriers and it may be that the presence of this genotype confers an increased risk of cellular damage from oxidative stress and promotes neural inflammation (112, 113). OSA may lead to early changes in the biomarkers of AD, which are potentially modifiable (102, 114). These include a wide array of cerebrospinal fluid and blood biomarkers such as amyloid-β, tau proteins, inflammatory cytokines, acute-phase proteins, antioxidants, homocysteine, and clusterin (102, 115, 116).…”
Section: Sleep Apnea and Cognitive Decline/dementiamentioning
confidence: 99%
“…OSA may lead to early changes in the biomarkers of AD, which are potentially modifiable (102, 114). These include a wide array of cerebrospinal fluid and blood biomarkers such as amyloid-β, tau proteins, inflammatory cytokines, acute-phase proteins, antioxidants, homocysteine, and clusterin (102, 115, 116).…”
Section: Sleep Apnea and Cognitive Decline/dementiamentioning
confidence: 99%
“…Recently, it has been shown that neurological consequences of obstructive sleep apnea (OSA) are similar to those found in Alzheimer's disease. Thus OSA would be one of the possible causes of Alzheimer's disease, with similar biomarkers for both diseases [5][6][7] . One hypothesis is that chronic intermittent hypoxia and sleep fragmentation might release several compounds inducing a neurotoxicity, which help to contribute to the progression of neurodegeneration.…”
Section: Sera Of Elderly Obstructive Sleep Apnea Patients Alter Bloodmentioning
confidence: 99%